Modificaciones en la corteza de Prosopis laevigata por el establecimiento de Tillandsia recurvata - Aguilar Rodriguez, S.=700 1 Terrazas, T.; Aguirre Leon, E.
(En, Es)
ilus., 30 ref.
Keywords: ANATOMIA DE LA PLANTA; CORTEZA; EPIFITAS; PROSOPIS; MEXICO; TILLANDSIA RECURVATA